A Phase I, Randomized, Double‐Blind, Placebo‐Controlled, Single‐Dose and Multiple‐Rising‐Dose Study of the BTK Inhibitor TAK‐020 in Healthy Subjects - Ehsanollah Esfandiari; Mary Chen; Glennda Smithson; Derek Blair; Helene Faessel; John Wagner; Lachy Mclean; Eric R. Fedyk (Wiley, 2021)
Bruton's tyrosine kinase (BTK) is a target for treatment of hematologic malignancies and autoimmune diseases. TAK‐020 is a highly selective covalent BTK inhibitor that inhibits both B cell receptor and fragment crystallizable receptor signaling. We assessed the safety/tolerability and pharmacokinetics/pharmacodynamics (PDs) of TAK‐020 in healthy subjects. Each cohort of the single‐rising dose (n = 72; 9 cohorts) and the multiple‐rising dose (n = 48; 6 cohorts) portions of the study comprised six TAK‐020‐treated and two placebo‐treated, subjects aged 18-55 years (inclusive). The PD effects were assessed by measuring BTK occupancy and the inhibition of fragment crystallizable epsilon receptor 1 (FcεRI)‐mediated activation of basophils. Overall, treatment‐emergent adverse events (TEAEs) were similar to placebo; there were no serious TEAEs or no TEAEs leading to discontinuation. TAK‐020 was rapidly absorbed (median time to maximum plasma concentration (Tmax) 45-60 minutes) with a half‐life of ~ 3-9 hours at doses ≥ 2.5 mg. TAK‐020 exposure was generally dose proportional for single doses ≤ 70 mg and after multiple doses of ≤ 60 mg once daily. Target occupancy was dose dependent, with doses ≥ 2.5 mg yielding maximum and sustained occupancy > 70% for > 96 hours. Single doses ≥ 4.4 mg reduced FcεRI‐mediated activation of basophils by > 80% and comparable inhibition was observed with daily dosing ≥3.75 mg for 9 days. Inhibition persisted for 24-72 hours postdose and the duration generally increased with dose. TAK‐020 was generally well‐tolerated in healthy subjects after single and multiple doses and demonstrated target engagement and pathway modulation. The PD effects outlasted drug exposures, as expected for covalent inhibition of BTK.